2003
DOI: 10.1037/0022-3514.84.6.1236
|View full text |Cite
|
Sign up to set email alerts
|

The do re mi's of everyday life: The structure and personality correlates of music preferences.

Abstract: The present research examined individual differences in music preferences. A series of 6 studies investigated lay beliefs about music, the structure underlying music preferences, and the links between music preferences and personality. The data indicated that people consider music an important aspect of their lives and listening to music an activity they engaged in frequently. Using multiple samples, methods, and geographic regions, analyses of the music preferences of over 3,500 individuals converged to revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

124
1,403
28
65

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,156 publications
(1,620 citation statements)
references
References 73 publications
124
1,403
28
65
Order By: Relevance
“…Specifically, we conducted a factor analysis on the current five genres, finding that jazz and classical music loaded on one dimension, techno and Latin American on a second dimension, and pop/rock on a third, separate dimension. This finding is reminiscent of the findings by Rentfrow and Gosling (2003), who found that both jazz and classical music loaded highly on a Complex/Reflective factor, electronic music such as techno on an Energetic factor, and rock on a separate factor named Rebellious. From these patterns, we created three emotion composites, a complex/reflective emotion composite-the average of the tender longing, amazement, spirituality, and peacefulness scales; an energy/activation compositeaveraging across activation terms; and a rebellious emotion composite-the average of revolt and anger-related terms.…”
Section: Emotions Induced By Various Musical Genressupporting
confidence: 68%
See 1 more Smart Citation
“…Specifically, we conducted a factor analysis on the current five genres, finding that jazz and classical music loaded on one dimension, techno and Latin American on a second dimension, and pop/rock on a third, separate dimension. This finding is reminiscent of the findings by Rentfrow and Gosling (2003), who found that both jazz and classical music loaded highly on a Complex/Reflective factor, electronic music such as techno on an Energetic factor, and rock on a separate factor named Rebellious. From these patterns, we created three emotion composites, a complex/reflective emotion composite-the average of the tender longing, amazement, spirituality, and peacefulness scales; an energy/activation compositeaveraging across activation terms; and a rebellious emotion composite-the average of revolt and anger-related terms.…”
Section: Emotions Induced By Various Musical Genressupporting
confidence: 68%
“…A more integrative picture of the manifold differences depicted in Figure 1 can be obtained by reorganizing the current data using procedures similar to those employed by Rentfrow and Gosling (2003) in their research on music preferences. Specifically, we conducted a factor analysis on the current five genres, finding that jazz and classical music loaded on one dimension, techno and Latin American on a second dimension, and pop/rock on a third, separate dimension.…”
Section: Emotions Induced By Various Musical Genresmentioning
confidence: 99%
“…We measured musical preferences with the Revised Short Test of Music Preferences (STOMP-R; Rentfrow & Gosling, 2003). This scale asks people to indicate their preference for 23 genres of music on a seven-point scale, from 1 (Dislike Strongly) to 7 (Like Strongly), that represent four higher-order dimensions of music preference: Intense and Rebellious (e.g., alternative, heavy metal, and rock), Upbeat and Conventional (e.g., country, gospel, and oldies), Energetic and Rhythmic (e.g., electronica, hip-hop, and reggae), and Reflective and Complex (e.g., blues, classical, and folk).…”
Section: Music Preferencesmentioning
confidence: 99%
“…Openness to experience showed a large effect (β = .39) and neuroticism showed a modest effect (β = .15; see Table 4) on how often people experienced musical imagery, consistent with past research ( Floridou et al, 2012 andKellaris, 2003). People high in openness listen to music more frequently ( Rentfrow & Gosling, 2003) and are more engaged with music (e.g., playing an instrument, going to concerts; Nusbaum & Silvia, 2011b), however, so it's not surprising that they should report hearing musical imagery more often. Note: n = 190.…”
Section: Personality and Musical Imagerymentioning
confidence: 99%
“…The rationale behind the choice of the FFM for AL is that these factors account for most of the variance among users in terms of trait terms [3]. Previous research has shown that personality influences human behaviours and that there exist direct relations between personality and tastes / interests [19]. Consequently, the incorporation of human personality into AL can help in selecting "good" items to be rated by the user.…”
Section: Introductionmentioning
confidence: 99%